Synthesis of Silver/Zinc@Lignin nanoparticles using peanut shells: photocatalytic and biological activity - Mahshid Shafiee; Zahra Sabouri; Asma Mostafapour; Majid Darroudi (AMB Express)
Abstract In this paper, zinc and silver-doped lignin nanoparticles (Ag/Zn@Lignin nanoparticles) were synthesized in two steps using peanut outer shells. The optical properties of NPs were analyzed through UV–Vis and PL measurements, while X-ray analysis approved their crystal structure. The surface characteristics and chemical composition of NPs were identified using FTIR analysis. TEM images of Ag/Zn@Lignin nanoparticles showed spherical morphology with an average size of about 22.71 nm. The antibacterial activity of Ag/Zn@Lignin nanoparticles was assessed against gram-negative and gram-positive bacteria, and the results exhibited strong antibacterial properties against the pathogenic strain compared to the standard. The MTT test results indicated that Ag/Zn@Lignin nanoparticles were more sensitive against cancer cells (Huh-7) in comparison with normal cells (L929), and IC50 values were reported as 122.9 and 389 µg/mL in order. Also, photocatalytic effects displayed the high ability of Ag/Zn@Lignin nanoparticles to degrade organic pigments such as Rhodamine B (98.8%, RhB) and Methylene blue (98.8%, MB) under UV light. Graphical abstract